PRINSIP PENGEMBANGAN KURIKULUM BERBASIS MULTIKULTURAL - Sauqi Futaqi (MIDA : Jurnal Pendidikan Dasar Islam, 2022)
Abstract This paper attempts to formulate the principles of multicultural-based curriculum development. This principle is indispensable in the process of curriculum formulation in the context of the national education system, especially in the midst of a multicultural Indonesian society. This paper aims to find the principles that will be used as the basis for curriculum development. Through several relevant literature reviews, there are two categories of principles, namely general and specific. The general principles relate to the domain of curriculum development in general. While the special principles relate to multicultural insight. Keywords: Principles, Curriculum Development, Multicultural. Abstrak Tulisan ini berupaya merumuskan prinsip-prinsip pengembangan kurikulum berbasis multikultural. Prinsip ini sangat diperlukan dalam proses perumusan kurikulum dalam konteks sistem pendidikan nasional, terlebih di tengah masyarakat Indonesia yang multikultural. Tulisan ini bertujuan menemukan prinsip-prinsip yang akan dijadikan dasar bagi pengembangan kurikulum. Melalui beberapa kajian pustaka yang relevan, ada dua kategori prinsip, yakni umum dan khusus. Prinsip umum berhubungan dengan domain pengembangan kurikulum pada umumnya. Sedangkan prinsip khusus berhubungan dengan wawasan multikultural. Kata Kunci: Prinsip, Pengembangan Kurikulum, Multikultural